2019
DOI: 10.3390/jcm8050647
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Hyperactivity and Inattention between Adolescents Participating and Non-Participating in A National Polish After-School Athletics Program

Abstract: Among the hyperactivity and inattention components, being predictors of the Attention Deficit Hyperactivity Disorder (ADHD) phenotype, there are restlessness, fidgeting, distractibility, lack of reflectiveness and lack of attention components. So far, it was observed that they may be associated with an excessive body mass in children. The aim of the study was to analyze differences of the hyperactivity and inattention between adolescents participating and non-participating in a national Polish after-school ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…About this, we observed that less than half of boys and girls with ADHD achieved the PA recommendations for health. This finding is consistent with the literature since children with ADHD between 6 and 17 years of age tend to participate less in PA and organized sports than their peers (Aranas & Leighton, 2022; Głąbska et al, 2019; Rommel et al, 2015). Regarding the amount of PA those students performed in the PE class, it should be noted that 11.4% of boys with ADHD never engaged in the PE classes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…About this, we observed that less than half of boys and girls with ADHD achieved the PA recommendations for health. This finding is consistent with the literature since children with ADHD between 6 and 17 years of age tend to participate less in PA and organized sports than their peers (Aranas & Leighton, 2022; Głąbska et al, 2019; Rommel et al, 2015). Regarding the amount of PA those students performed in the PE class, it should be noted that 11.4% of boys with ADHD never engaged in the PE classes.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, children who practice more PA show better performance in executive functions, including working memory, inhibition, and speed of information processing, and it also, improves academic performance, behavior, self-esteem, and relationships with peers (Chan et al, 2022; Christiansen et al, 2019; Cook et al, 2015; de Greeff et al, 2018; Głąbska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The #goathletics Study was conducted with the cooperation of (1) the Institute of Human Nutrition Sciences, Warsaw University of Life Sciences (SGGW-WULS) (responsible for the assessment of body weight and food habits), (2) Józef Piłsudski University of Physical Education (responsible for assessment of physical fitness), (3) the Polish Athletic Association (responsible for Athletics for All training groups), and (4) the Nutrition, Health and Wellness Unit, Nestlé Polska S.A. (responsible for Athletics for All program as one of the founders). Within the #goathletics Study, a Polish national extracurricular athletics program (Athletics for All) is assessed [17][18][19].…”
Section: Ethical Backgroundmentioning
confidence: 99%